Silverlight 2 for ASP.NET Developers - Swift Jonathan; Barker Chris; Wahlin Dan; Alvarez Patuel Sanvador (USA : Wiley Publishing, Inc, 2009)
Chapter 1: Silverlight in a Nutshell
Chapter 2: Silverlight Architecture
Chapter 3: XAML Condensed
Chapter 4: Programming Silverlight
Chapter 5: Creating the user interface
Chapter 6: Silverlight controls
Chapter 7: Styles and Templates
Chapter 8: User interaction
Chapter 9: Communicating with the Server
Chapter 10: Working with data
Chapter 11: Creating Custom Sontrols
Chapter 12: Securing your silverlight application
Chapter 13: Audio and Video
Chapter 14: Graphics and Animation
Chapter 15: Troublesshooting
Chapter 16: Performance
Part 2: Developing ASP.NET Applications with Silverlight
Keywords: ASP.NET; Afghanistan --Geography.; Silverlight 2